2022
DOI: 10.1038/s41598-022-25557-9
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in presenting symptoms and signs of dry eye disease in Norway

Abstract: The study investigated the seasonal variations of presenting symptoms and signs of dry eye disease (DED) in Norway. 652 consecutive DED patients examined between August 2012 and May 2015 in Oslo, Norway, were included. Presenting symptoms and signs were related to the season according to when each patient was examined. Weather report data from the examination day were compared with the presenting symptoms and signs. Oslo's mean seasonal temperatures during spring, summer, fall, and winter were 6.4 °C, 15.6 °C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Other investigations have indicated that seasonal changes in temperature, wind, and sunshine may all exacerbate DED. [16][17][18][19][20][21] Eidet et al 20 examined and interviewed 652 patients to determine a possible seasonality of signs and symptoms in DED, and found that neither DED severity level nor DED symptoms differed seasonally in Oslo, Norway. However, some parameters for DED showed seasonal variations (Schirmer test and tear meniscus height).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigations have indicated that seasonal changes in temperature, wind, and sunshine may all exacerbate DED. [16][17][18][19][20][21] Eidet et al 20 examined and interviewed 652 patients to determine a possible seasonality of signs and symptoms in DED, and found that neither DED severity level nor DED symptoms differed seasonally in Oslo, Norway. However, some parameters for DED showed seasonal variations (Schirmer test and tear meniscus height).…”
Section: Discussionmentioning
confidence: 99%
“…Tear meniscus level is closely associated with the pathology, signs, and symptoms of DED, 10 and these signs and symptoms may worsen with different seasons. [16][17][18][19][20][21] Ophthalmic practitioners often encounter patients complaining of dryness or other ocular surface symptoms in the drier seasons of winter and fall; however, little is known about which sign corresponds to which symptom in these seasons. Furthermore, the seasonality of tear meniscus level has not been determined.…”
Section: Introductionmentioning
confidence: 99%